Mass transfer in bubble column reactors: effect of bubble size distribution - Kulkarni, Amol A. (Industrial & Engineering Chemistry Research, 2007)
Mass transfer in a bubble column is analyzed in a different perspective. The experiments were performed in a bubble column reactor that was operated in a regime where the overall rate of absorption of gas into liquid was dependent on both the mass-transfer coefficient and the rate of reaction. Homogeneous catalytic oxidation of sodium sulfite was considered as a model reaction. The local instantaneous velocity data was measured using LDA in the presence of reaction and was used to yield the bubble size distribution at several locations in the column. The role of individual bubble size during mass transfer with chemical reaction was observed to vary. The findings suggest that a narrow bubble size distribution would help to achieve uniformity in the performance at bubble scale, so that an identical regime of mass transfer with reaction exists at the individual bubble level.